Pengembangan Ide Bisnis bagi Kelompok Wanita Tani, Kelurahan Sei Selincah Palembang - Sulastri, Sulastri; Adam, Mohamad; Saftiana, Yulia; Hamdaini, Yulia (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: To provide literacy for the development of business ideas for the Women Farmers Group in Sei Selincah Village, Palembang. Methodology/approach: The activity stages begin with (1) mapping to identify community needs and local potential; (2) simulation to make products (3) reviewing several examples of product result 4) training (5) mentoring for potential products; and (6) evaluation. Results/findings: The results of the difference test of the activities before and after training showed a positive increase for 11 out of 14 question materials and 3 question materials before and after training, the results were relatively the same. However, statistically, the Wilcoxon Test as a whole showed a significant difference with a value of 0.003 ? 0.05. Conclusion: This PKM activity contributed to increasing income and capabilities of the Women Farmers Group while building networks with academia for sustainable business development. Limitations: The level of community participation in this activity is not optimal and participants are limited to homogeneous age groups. Contribution: Practice in entrepreneurship science in the topic of creativity in developing business ideas. Conclusion: This activity motivates Women Farmers Groups for new businesses in more targeted ways and can increase the utilization of potential agricultural products around them.